2016
DOI: 10.1016/j.neuroimage.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Intersession reliability of population receptive field estimates

Abstract: Population receptive field (pRF) analysis is a popular method to infer spatial selectivity of voxels in visual cortex. However, it remains largely untested how stable pRF estimates are over time. Here we measured the intersession reliability of pRF parameter estimates for the central visual field and near periphery, using a combined wedge and ring stimulus containing natural images. Sixteen healthy human participants completed two scanning sessions separated by 10–114 days. Individual participants showed very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 48 publications
11
72
0
Order By: Relevance
“…Functional magnetic resonance imaging was employed to quantify spatial parameters of the pRFs, by eliciting a wave of visual excitation along the visual cortex (Engel, 1997;Engel et al, 1994). Using a variety of stimulation protocols (Dumoulin & Wandell, 2008;Greene, Dumoulin, Harvey, & Ress, 2014;Sereno et al, 1995) and estimation methods (direct fit, topographic fit), the spatial pRF properties such as of location and size (Amano, Wandell, & Dumoulin, 2009;Zuiderbaan, Harvey, & Dumoulin, 2012) could be estimated throughout the visual system with a high degree of intrasubject reliability (van Dijk, de Haas, Moutsiana, & Schwarzkopf, 2016).…”
mentioning
confidence: 99%
“…Functional magnetic resonance imaging was employed to quantify spatial parameters of the pRFs, by eliciting a wave of visual excitation along the visual cortex (Engel, 1997;Engel et al, 1994). Using a variety of stimulation protocols (Dumoulin & Wandell, 2008;Greene, Dumoulin, Harvey, & Ress, 2014;Sereno et al, 1995) and estimation methods (direct fit, topographic fit), the spatial pRF properties such as of location and size (Amano, Wandell, & Dumoulin, 2009;Zuiderbaan, Harvey, & Dumoulin, 2012) could be estimated throughout the visual system with a high degree of intrasubject reliability (van Dijk, de Haas, Moutsiana, & Schwarzkopf, 2016).…”
mentioning
confidence: 99%
“…The pRF center position and size were expressed in dva. The estimation procedure was identical to our previous studies (Moutsiana et al, 2016; van Dijk et al, 2016). The resulting parameter maps were modestly smoothed with a spherical Gaussian kernel (FWHM = 3 mm; for experiment-specific smoothing procedures of pRF and response data, see 3.1.7 Data analysis).…”
Section: Methodsmentioning
confidence: 99%
“…The pRF parameters at each vertex were fit using a two-stage procedure. First, we applied a coarse fit which involved an extensive grid search by correlating the actually observed time series against a set of 7650 predicted time series derived from a combination of x 0 , y 0 , and  covering the plausible range for each parameter (see van Dijk et al, 2016). The parameters giving rise to the maximal correlation were then retained for the second stage, the fine fit, provided the squared correlation, R 2 , exceeded 0.01.…”
Section: Prf Modellingmentioning
confidence: 99%
“…The indirect nature of estimating pRFs from fMRI data suggests therefore that there could be considerable variability in derived measurements. Direct test-retest evaluations with the same experimental setup have shown that pRF mapping experiments are robust and repeatable (Senden et al, 2014;van Dijk et al, 2016;Benson et al, 2018). However, for different experimental setups, for instance, in terms of the magnetic field strength and the particular pulse sequence used to acquire fMRI data the comparability has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation